Interaction between bank branches, local entrepreneurship and development on rural and suburban areas Regional Unity of Serres - Chrysanthi Balomenou; Marianthi Maliari; Dimitris Lagos (European Regional Science Association (ERSA), 2012)
This paper is divided into two parts, one theoretical and one empirical and attempts to examine the interaction between bank branches, local entrepreneurship and development on rural and suburban areas at Regional Unity of Serres, Central Macedonia, Greece. More particularly, in the first part of our paper are presented loan providing funds for SMEs in Greece, the new law for local authorities named "Kallikratis" on Regional Unity of Serres, local demographic characteristics and the existing bank branches network on this area. Analyzing the data we conclude to the characterization of the region as rural and underdevelopment. At the second part are presented the results of our questionnaire-based research from 74 entrepreneurs in Regional Unity of Serres. It is noticeable that businessmen's answers are similar to those deduced from the results of the researches that have been referred to in bibliography Finally we will end this presentation with the main conclusions providing that an extensive network of bank branches on rural and suburban areas support local entrepreneurship and contribute to local development.
Keywords: 330